Está en la página 1de 6

Anexo D

Tabla de Integrales
(PUEDE SUMARSE UNA CONSTANTE ARBITRARIA A CADA INTEGRAL)

1
xn+1
n+1

1.

xn dx =

2.

1
dx = log | x |
x

3.

ex dx = ex

4.

ax dx =

5.

sen x dx = cos x

6.

cos x dx = sen x

7.

tan x dx = log |cos x|

8.

cot x dx = log |sen x|

9.

(n != 1)

ax
log a

1
1

x +
sec x dx = log |sec x + tan x| = log tan
2
4
227

228

Tabla de Integrales

10.

11.

csc x dx = log |csc x cot x| = log tan x


2
arcsen

x
x 2
dx = x arcsen
+ a x2
a
a

12.

arccos

x
x
dx = x arccos a2 x2
a
a

13.

arctan

14.

sen2 mx dx =

1
(mx sen mx cos mx)
2m

15.

cos2 mx dx =

1
(mx + sen mx cos mx)
2m

16.

sec2 x dx = tan x

17.

csc2 x dx = cot x

18.

19.

20.

21.

22.

23.

24.

senh x dx = cosh x

25.

cosh x dx = senh x

(a > 0)

(a > 0)

x a
x
dx = x arctan log a2 + x2
a
a 2

(a > 0)

Z
senn1 x cos x n 1
senn2 x dx
+
sen x dx =
n
n
Z
cosn1 x sen x n 1
cosn2 x dx
+
cosn x dx =
n
n
Z
tann1 x
n
tan x dx =
tann2 x dx (n != 1)
n1
Z
cotn1 x
n
cotn2 x dx (n != 1)
cot x dx =
n1
Z
tan x secn2 x n 2
n
sec x dx =
+
secn2 x dx (n != 1)
n1
n1
Z
cot x csc n1 x n 2
n
+
cscn2 x dx (n != 1)
csc x dx =
n2
n1
n

229

26.

tanh x dx = log |cosh x|

27.

coth x dx = log |sen hx|

28.

sech x dx = arctan (senh x)

29.

30.

1
1
senh2 x dx = senh 2x x
4
2

31.

1
1
cosh2 x dx = senh 2x + x
4
2

32.

sech2 x dx = tanh x

x
cosh x + 1
1

csch x dx = log tanh = log


2
2
cosh x 1

x
x
dx = xsenh1 x2 a2 (a > 0)
a
a

Z
xcosh1 xa x2 a2 cosh1 xa > 0, a > 0
1 x
34.
cosh
dx =
xcosh1 xa + x2 a2 cosh1 xa < 0, a > 0
a
Z

x a
x
35.
tanh1 dx = xtanh1 + log a2 x2
a
a 2
Z

1
x

36.
dx = log x + a2 + x2 = sen h1
(a > 0)
a
a2 + x2
Z
1
x
1
dx = arctan
(a > 0)
37.
a2 + x2
2
a
Z
x 2
a2
x
a2 x2 dx =
a x2 + arcsen
38.
(a > 0)
2
2
a
Z
2
3

x 2
3a4
x
a 2 x2 +
a x2 2 dx =
39.
5a 2x2
arcsen
(a > 0)
8
8
a
Z
x
1

(a > 0)
dx = arcsen
40.
a
a2 x2

Z
a + x
1
1

log
dx =
41.
a2 x2
2a
a x
33.

senh1

230

42.

Tabla de Integrales
Z

1
(a2 x2 )

3
2

dx =

a2

x
a2 x2

x 2
a2

x a2 log x + x2 a2
2
2
Z

1
x

(a > 0)
44.
dx = log x + x2 a2 = cosh1
2
2
a
x a

Z
x
1
1

45.
dx = log
x(a + bx)
a
a + bx
43.

x2 a2 dx =

2 (3bx 2a) (a + bx) 2


46.
x a + bx dx =
15b2
Z
Z

1
a + bx

47.
dx = 2 a + bx + a
dx
x
x a + bx

Z
2 (bx 2a) a + bx
x

dx =
48.
3b2
a + bx

a+bx
a
Z

1 log

(a > 0)
1
a
a+bx+
q a

dx =
49.
2 arctan a+bx (a > 0)
x a + bx
Z

50.

51.

a + a2 x2
a2 x2
2
2

dx = a x a log

x
x

3
1
x a2 x2 dx = a2 x2 2
3

x 2
a4
x
x2 a2 x2 dx =
a2 x2 + arcsen
2x a2
8
8
a

Z
a + a2 x2
1
1

dx = log
53.

a
x
x a2 x2
Z

54.
dx = a2 x2
a2 x2
Z
x2
x
a2
x 2

55.
(a > 0)
a x2 + arcsen
dx =
2
2
2
2
a
a x

Z 2
a + x2 + a2

x + a2

56.
dx = x2 + a2 a log

x
x
52.

(a > 0)

231

57.

a
x2 a 2
dx = x2 a2 a arccos
= x2 a2 arcsec
x
|x|
a

(a > 0)

3
1 2
x a2 2
x x2 a2 dx =
3

1
x
1

dx = log
59.
a
x x2 + a2
a + x2 + a2
Z
1
1
a

dx = arccos
60.
(a > 0)
2
2
a
|
x
|
x x a

Z
1
x2 a2

61.
dx =
a2 x
x2 x2 a2
Z

dx = x2 a2
62.
x2 a 2

Z
2ax+b
1
b2 4ac

log 2ax+b+ b2 4ac (b2 > 4ac)


1
b2 4ac
dx
=
63.
ax2 + bx + c
2
arctan 2ax+b
(b2 < 4ac)
4acb2
4acb2
Z
Z
2

x
1
b
1

64.
dx =
log ax + bx + c
dx
2
2
ax + bx + c
2a
2a
ax + bx + c
(

Z
1 log |2ax + b + 2 a ax2 + bx + c| (a > 0)
1
a

dx =
65.
2axb
1 arcsen
(a < 0)
ax2 + bx + c
a
b2 4ac
Z
Z
2ax + b 2
4ac b2
1
2

ax + bx + c dx =
ax + bx + c +
dx
66.
2
4a
8a
ax + b + c

Z
Z
x
ax2 + bx + c
b
1

67.
dx =
dx

2
2
a
2a
ax + bx + c
ax + bx + c
2

(
Z
2 c ax +bx+c+bx+2c
1
log
1
(c > 0)
x
c

dx =
68.
1
bx+2c
2
arcsen

(c < 0)
x ax + bx + c
c
|x| b2 4ac

58.

q
2
1
2
2
69.
x x2 + a2 dx =
x a
(a2 + x2 )3
5
15
q
Z 2
2
(x2 a2 )3

x a
dx =
70.
x4
3a2 x3
Z
sen(a b)x sen(a + b)x
71.
sen ax sen bx dx =

2(a b)
2(a + b)
Z

a2 != b2

232

Tabla de Integrales

72.

sen ax cos bx dx =

cos(a b)x cos(a + b)x

2(a b)
2(a + b)

73.

cos ax cos bx dx =

sen(a b)x sen(a + b)x

2(a b)
2(a + b)

74.

sec x tan x dx = sec x

75.

csc x cot x dx = csc x

76.

a2 != b2

a2 != b2

Z
cosm1 x senn1 +x m 1
+
cosm2 x senn x dx =
cos x sen x dx =
m+n
m+nZ
n1
senn1 x cosm+1 x
+
cosm x senn2 x dx
=
m+n
m+n
Z
n
1
xn1 cos ax dx
xn sen ax dx = xn cos ax +
a
a
Z
1 n
n
n
x cos ax dx = x sen ax
xn1 sen ax dx
a
a
Z
xn eax n
n ax
x e dx =
xn1 eax dx

a
a

1
n
n+1 log ax

x log(ax) dx = x
n+1
(n + 1)2
Z
m
xn+1
m
m
n
(log ax)
x (log ax) dx =
xn (log ax)m1 dx
n+1
n+1
m

77.

78.

79.

80.

81.

82.

eax sen bx dx =

eax (a sen bx b cos bx)


a2 + b2

83.

eax cos bx dx =

eax (b sen bx + a cos bx)


a2 + b2

84.

sech x tanh x dx = sech x

85.

csch x coth x dx = csch x